Potential Value of Customized Video Self-Modelling for Motor Skill Learning in Individuals with Cerebral Palsy: A Case-Study Approach. Issue 4 (August 2021) - Steel, Kylie A.; Anderson, David I.; Smith, Caroline A.; Ellem, Eathan; Liu, Karen P. Y.; Morrison-Gurza, Andrew; Dune, Tinashe; Fairley, Lauren H.
Cerebral Palsy (CP) is a common physical disability that is managed with a variety of strategies. One non-invasive intervention for people living with CP is a type of video self-modelling (VSM) referred to as positive self-review (PSR). PSR involves watching a video of oneself performing only the best examples of a desired task; this technique has been associated with improved performance and learning for people without disabilities and for those in various clinical populations, including children with spina bifida and stroke patients. PSR may have similar benefits for people living with CP. In this study we examined the effectiveness of PSR for improving a self-selected movement task among individuals living with CP. In this case study approach, eight participants completed a pre-, post-, and second post-test measuring and recording well-being, movement self-consciousness and tendency to consciously monitor movements. Results were mixed, with some participants improving their movement time, well-being ratings and tendency toward self-consciousness and conscious monitoring of movements and others showing no changes or regressions. The effectiveness of VSM appears to depend upon the match between type of task and disability and/or the length of practice. More study is needed.